C - H ⋯ 0 and N - H ⋯ 0 hydrogen bonds in liquid amides investigated by monte carlo simulation - Cordeiro, João M. Marques [UNESP] (Wiley, 1997)
Monte Carlo simulations of liquid formamide, N-methylformamide (MF), and N, N-dimethytformamide (DMF) have been performed in the isothermal and isobaric ensemble at 298 K and 1 atm, aiming to investigate the C-H ⋯ O and N-H ⋯ O hydrogen bonds. The interaction energy was calculated using the classical 6-12 Lennard-Jones pairwise potential plus a Coulomb term on a rigid six-site molecular model with the potential parameters being optimized in this work. Theoretical values obtained for heat of vaporization and liquid densities are in good agreement with the experimental data. The radial distribution function [RDF, g(r)] obtained compare well with R-X diffraction data available. The RDF and molecular mechanics (MM2) minimization show that the C-H ⋯ O interaction has a significant role in the structure of the three liquids. These results are supported by ab initio calculations. This interaction is particularly important in the structure of MF. The intensity of the N - H ⋯ O hydrogen bond is greater in the MF than formamide. This could explain some anomalous properties verified in MF. © 1997 John Wiley & Sons, Inc.
Keywords: Amides; Hydrogen bond; Monte Carlo simulation; Radial distribution functions